IMPLEMENTATION OF GUIDED INQUIRY MODEL IN REACTION RATE MATTER TO TRAIN CRITICAL THINKING SKILL (Universitas Negeri Surabaya, 2020)
The purpose of the research are to know learning outcomes of critical thinking skill and students responses to the implementation of the guided inquiry learning model. Type of research is a pre-experimental. The instruments used were implementation of learning sheet, student activity sheet, test sheet and student response questionnaire. The results showed that (1) The implementation of the guided inquiry learning model to train critical thinking skills at meetings 1 to 3 was 95.24%; 96.15% and 90.87%. (2) Individual completeness of critical thinking skills reaches 94.44% with very good predicate and 5.56% with good predicate. The critical thinking skill of the high category inference component was 97.22% and the medium category was 2.78%; the analysis component of the high category was 94.44% and the medium category was 5.56%; the high category explanation component was 55.56% and the medium category was 44.44%. (3) Positive responses of students to the guided inquiry learning model of 88.91%. Keyword : Guided Inquiry, Critical Thinking Skill, Reaction Rate